Artefact expression associated with several cone‐beam computed tomographic machines when imaging root filled teeth. (15th November 2014) - Vasconcelos, K. F.; Nicolielo, L. F. P.; Nascimento, M. C.; Haiter‐Neto, F.; Bóscolo, F. N.; Van Dessel, J.; EzEldeen, M.; Lambrichts, I.; Jacobs, R.
Abstract Aim To evaluate the characteristic artefact patterns associated with teeth root filled with Gutta‐percha when scanned with four cone‐beam CT devices. Methodology Whilst using soft tissue simulation, ten root filled human premolars were placed in empty sockets in a dry human skull. Subsequently, the skull was scanned using 3D Accuitomo 170®, WhiteFox®, Cranex 3D® and Scanora 3D® following clinical protocols with the highest resolution and artefact reduction. After proper image registration in OnDemand3D® software (Cybermed, Seoul, Korea), each image slice was evaluated by three trained and calibrated dentomaxillofacial radiologists, which scored absence (0) and presence (1) of cupping artefact, hypodense halos and streak artefacts. Kappa test was performed for intra‐ and interobserver agreement. Results A moderate to perfect agreement for each observer (intra‐observer κ = 0.5–1.0) was found. Agreement between the different observers was moderate to almost perfect for the different artefact patterns (interobserver κ = 0.55–0.9). Cupping artefact was the most prevalent (70%), followed by a hypodense halo (35%) and streak artefacts (16%). The Chi‐squared test revealed significantly more streaks in axial slices (P < 0.0001), with some CBCT systems yielding significantly inferior results to others (P < 0.05). The dedicated EndoMode and artefact reduction did not improve the result significantly. Conclusions The variation of artefact expression was significantly different amongst CBCT machines for root filled teeth. Continuous efforts are needed to improve CBCT reconstruction algorithms, with a specific focus on reducing artefacts induced by dense dental materials, whilst striving for enhanced image quality at low‐radiation doses.